Effect of dietary Chinese herbal preparation on dry matter intake, milk yield and milk composition, serum biochemistry, hematological profile, and reproductive efficiency of Holstein dairy cows in early postpartum period - Abulaiti, Adili; Ahsan, Umair; Naseer, Zahid; Ahmed, Zulfiqar; Liu, Wenju; Ruan, Chongmei; Pang, Xunsheng; Wang, Shujuan (Frontiers in Veterinary Science, 2024)
The present study investigated the effects of various inclusion levels of dietary Chinese herbal medicine (CHM) preparation on feed consumption, milk yield and milk composition, serum biochemistry, hematological profile, and reproductive efficiency of Holstein dairy cows. A total of 117 lactating Holstein cows were randomly divided into four groups as control (n = 27; without CHM supplementation) and treatment groups CHM-0.5 (n = 31), CHM-0.75 (n = 29), and CHM-1 (n = 30) fed diet supplemented with 0.5, 0.75, and 1 kg/cow/d for 30 days, respectively. The study began at d 20 postpartum (d 0 of the study). At d 50 postpartum, the cows in all groups were subjected to estrus synchronization using a modified Ovsynch protocol (GPGMH) and observed for reproductive variables. Feed intake, milk yield and milk composition, serum biochemistry and hematological profile, and reproductive efficiency were measured. A significantly higher milk yield with improved milk lactose, milk protein and milk fat were found in the CHM-0.75 group compared to the other groups (P < 0.05). Besides, the estrus response, ovulation rate, ovulatory follicle diameter, and pregnancy rate increased in CHM-0.75 compared to CHM-0 or CHM-0.5 group (P < 0.05). The serum metabolites (glucose, AST, arginine, BUN, and NO) showed variations among the treatment groups at different time points (synchronization, AI, or post-AI). In conclusion, CHM supplementation improves the milk yield, milk composition, and serum metabolites in dairy cows. Daily supplementation of 0.75 kg CHM before the GPGMH protocol application enhances the reproductive traits in dairy cows under summer conditions.